Local-neighborhood effects of environmental regulations on green technology innovation in manufacturing: Green credit-based regulation - Jiang, Ling; Wang, Yuqi; Zhang, Jian (Frontiers in Environmental Science, 2022)
Under the pressure of environmental degradation and resource depletion, China's manufacturing industry faces the need for transformation and upgrade driven by technological innovation. However, environmental regulations (ERs) can help facilitate technological innovation. As an important financial support for the green innovation transformation of China's manufacturing industry, it is crucial to exploit the policy synergy between green credit (GC) and ERs at the regional level to stimulate the technological innovation effect. GC, as a financial instrument, can play a unique role in ERs; therefore, the relationship between ERs and the level of green technology innovation (GTI) based on the GC perspective deserves an in-depth study. We explored the spatial effects of ERs and GC on GTI in manufacturing and the moderating effects of GC policies on ERs affecting GTI using a spatial Durbin model for the panel data of 30 Chinese provinces from 2006 to 2016. We observed that ERs exerted a negative impact on local manufacturing GTIs and undermined the innovation effect in neighboring locations through spatial spillover effects. The development of GC helps stimulate the transformation of GTI in local manufacturing industries, further focusing on the effects of policy instruments and their combinations. The moderating effect of GC suggests that its development can weaken the inhibiting effect of ERs on GTI in local and neighboring areas and is particularly significant in coastal areas. Our study provides a theoretical basis and policy insight for coordinating government external intervention and market operation laws at the regional level to bring into play the incentive effect of technological innovation.